A Proposed guide for joint audits of financial statements - Ammar Khaleel Ibrahim; Fayhaa Abdulla Yaqoop (Journal of Madenat Alelem University College, 2020)
The aim of this research is to propose a guide that includes several axes to develop the audit process in accordance with the method of joint auditing in line with the international auditing standards, so that it can be applied in the auditing firms that conduct the joint audit. The guide includes many axes related to the responsibilities of the joint auditors, distribution and allocation of process efforts, conclusions and differences of opinion, so as to provide a unified approach to the audit process. The main results of the research are the absence of an international audit guide or standard that regulates the auditing process conducted in the joint audit method and this leads to many problems, including the risk of an auditor’s reliance on another as well as an unbalanced distribution of the work to be performed , while the main recommendations of the research are that it is necessary to adopt a guide related to the organization of the joint audit in the Iraqi environment by the Board of Audit profession in line with best practices recognized Internationally, in such a way as to improve the quality of external audit.